KEPUTUSAN PEMBELIAN PRODUK WARDAH MELALUI E-COMMERCE SHOPEE PERAN CITRA MEREK SEBAGAI VARIABEL MEDIASI - Aprilliyani, Reny; Kuswati, Rini (Program Studi Manajemen Pemerintahan dan Keuangan Daerah Fakultas Ekonomi dan Bisnis Universitas Jambi, 2024)
This study aims to analyze the effect of Price and Promotion on Purchasing Decisions. This research will fill the empirical GAP related to findings that do not fully support each other, there is research showing that price and promotion are significant determinants of purchasing decisions. Furthermore, price has a significant influence and becomes a benchmark for consumers before making purchasing decisions, while promotion is to attract consumer attention, as well as provide information about products and services and can influence consumer purchasing decisions. This research method is research with a quantitative deductive approach. The population in this study are people who allow using the Wardah brand. Respondents in this study were 160 people through an online survey using google form with a Likert scale. The sampling technique used non probability sampling with purposive sampling method. Data analysis using SMARTPLS. Validity and reliability tests using smart PLS analysis on the outer model. Hypothesis testing using the smartPLS inner model. The analysis results show that brand image partially mediates the effect of price on purchasing decisions and brand image partially mediates the effect of promotion on purchasing decisions.